The intraoperative use of aortic balloon occlusion technique for sacral and pelvic tumor resections: A case-control study. (March 2020) - Ratto, Nicola; Boffano, Michele; Pellegrino, Pietro; Conti, Andrea; Rossi, Laura; Verna, Valter; Rastellino, Valentina; Berardino, Maurizio; Piana, Raimondo
Abstract: Introduction: Pelvic and sacral tumor surgery is traditionally characterized by several major complications. Bleeding is probably the most feared and dreadful complication. The aim of the study was to evaluate whether the intraoperative use of the intra-aortic balloon occlusion technique could decrease the perioperative blood loss. A secondary aim was to assess aortic balloon-related complications. Materials and methods: From January 2014 to December 2017 15 patients (Group 1) treated with intra-aortic balloon inflation were prospectively enrolled and compared to a historical control group (Group 2) of 11 patients with similar surgeries. Number of blood units transfused, perioperative hemoglobin values, hours spent in intensive care unit (ICU), length of inpatient stay, and perioperative complications were evaluated. Results: Intraoperatively, a mean of 6.1 blood units per patient (BUPP) was used in Group 1 and 16.2 BUPP in Group 2. Postoperatively the averages were 2, 8 and 5, 4 BUPP in Group 1 and 2, respectively. Patients in Group 1 had a faster recovery in hemoglobin values, as well as a shorter length of overall inpatient stay (28, 9 vs 59 days) and of ICU stay (33.9 vs 74.6 h). The most relevant complications observed in Group 1 were two thrombosis at the incannulation site that required a surgical arterial thrombectomy. Conclusion: The intra-aortic balloon occlusion is an effective technique to control bleeding during the resections of huge pelvic and sacral tumors. A proper training of a multidisciplinary team and an accurate patient selection are required to prevent major complications. Highlights: Bleeding is one of the most feared and dreadful complications in pelvic and sacral tumor surgery. The use of intra-aortic balloon occlusion can decrease intraoperative bleeding, also reducing the need for blood transfusions. A faster patient recovery is shown in patients treated with intra-aortic balloon occlusion. The proposed algorithm could help in the selection of patients in which it is recommended to use this technique. A multi-specialist team needs to be trained to reduce complications linked to the procedure.